Seawater Carbonate Chemistry Distributions Across the Eastern South Pacific Ocean Sampled as Part of the GEOTRACES Project and Changes in Marine Carbonate Chemistry Over the Past 20 Years - Bates, Nicholas Robert (Frontiers in Marine Science, 2018)
The US GEOTRACES Eastern Pacific Zonal Transect in 2013 that sampled in the South Pacific Ocean has provided an opportunity to investigate the biogeochemical cycling of trace elements and isotopes (TEIs) and seawater carbon dioxide (CO2)–carbonate chemistry. Across the Peru to Tahiti section, the entire water column was sampled for total alkalinity (TA) and dissolved inorganic carbon (DIC), in addition to core hydrographic and chemical measurements conducted as part of the GEOTRACES cruise. From the nutrient-rich, low-oxygen coastal upwelling region adjacent to Peru to the oligotrophic central Pacific, very large horizontal gradients in marine carbonate chemistry were observed. Near the coast of Peru, upwelling of CO2-rich waters from the oxygen-deficient zone (ODZ) impinged at the surface with very high partial pressures of CO2 (pCO2; >800–1,200 μatm), and low pH (7.55–7.8). These waters were also undersaturated with respect to aragonite, a common calcium carbonate (CaCO3) mineral. These chemical conditions are not conducive to pelagic and shelf calcification, with shelf calcareous sediments vulnerable to CaCO3 dissolution, and to the future impacts of ocean acidification. A comparison to earlier data collected from 1991 to 1994 suggests that surface seawater DIC and pCO2 have increased by as much as 3 and 20%, respectively, while pH and saturation state for aragonite (Ωaragonite) have decreased by as much as 0.063 and 0.54, respectively. In intermediate waters (∼200–500 m), dissolved oxygen has decreased (loss of up to -43 μmoles kg-1) and nitrate increased (gain of up to 5 μmoles kg-1) over the past 20 years and this likely reflects the westward expansion of the ODZ across the central Eastern South Pacific Ocean. Over the same period, DIC and pCO2 increased by as much as +45 μmoles kg-1 and +145 μatm, respectively, while pH and Ωaragonite decreased by -0.091 and -0.45, respectively. Such rapid change in pH and CO2–carbonate chemistry over the past 20 years reflects substantial changes in the ODZ and water-column remineralization of organic matter with no direct influence from uptake of anthropogenic CO2. Estimates of anthropogenic carbon (i.e., CANT) determined using the TrOCA method showed no significant changes between 1993 and 2014 in these water masses. These findings have implications for changing the thermodynamics and solubility of intermediate water TEIs, but also for the marine ecosystem of the upper waters, especially for the vertically migrating community present in the eastern South Pacific Ocean.